1988
DOI: 10.3382/ps.0670327
|View full text |Cite
|
Sign up to set email alerts
|

Daily Output of Spermatozoa and Extragonadal Spermatozoal Reserves in Turkeys

Abstract: Daily spermatozoal output (DSO) was estimated by determining the total number of spermatozoa in ejaculates of male line breeder turkeys ejaculated daily for 15 days. The DSO was constant at 520 million spermatozoa after the first 6 days of semen collection. Testicular spermatozoal reserves (TSR) and extragonadal sperm reserves (EGR) were measured 24 h after the last semen collection from turkeys ejaculated 1 x/day for 15 consecutive days (ejaculated) and 21 days after the last semen collection from turkeys pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Our observations of significant differences between testes weight within individual male turkeys supported observations by Burke [34] and Cecil and Bakst [35,36]. Hocking [37] observed that the left testis was heavier than the right in 67% of the male chickens, but concluded that the differences in weights were minor.…”
Section: Discussionsupporting
confidence: 75%
“…Our observations of significant differences between testes weight within individual male turkeys supported observations by Burke [34] and Cecil and Bakst [35,36]. Hocking [37] observed that the left testis was heavier than the right in 67% of the male chickens, but concluded that the differences in weights were minor.…”
Section: Discussionsupporting
confidence: 75%
“…Significant mean values between treatments were compared by Duncan's multiple range test (Duncan, 1955). (Cecil et al, 1988) was quite feasible within the time frame of our investigation, supporting the possible integrity of the seminiferous tubules of the Cd-treated toms.…”
Section: Methodssupporting
confidence: 56%
“…These include the differences in the testicular architecture of their excurrent duct systems, especially the anatomical conformation of the ductus epjdidymis and the ductus deferens as well as the location of their spermatozoal storage sites (Tingari, 1972;Lake, 1984). The relatively shorter duration of spermatogenesis in birds (de Revier, 1968;Cecil et al, 1988) as compared to mammals and the variations in the physiological and biochemical reactivity of the tr male genital tracts (Munro, 1938;Erricsson and Baker, 1970;Jones et al, 1972) may also be relevant to the phenomenon. Whether such distinctions confer any specific biological advantages on avian species in their gonadal responses to Cd intoxication remains to be elucidated by further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The cloacal protuberance is formed from the two seminal glomerae, the bulbous, coiled parts of the vas deferens, which lie beneath the skin, dorso-lateral to the cloaca (King 1981;Lake 1981). Non-passerines also possess an enlarged distal portion of the vas deferens, which serves as a storage area for sperm (Bedford 1979;Lake 1981;Clulow and Jones 1982;Cecil et al 1988), but in contrast to passerines this lies within the body cavity and does not produce a protuberance, except in a few Psittaciformes (Samour et al 1986; see also Wolfson 1960).…”
Section: Introductionmentioning
confidence: 99%